Validity of accelerometry in assessing the duration of the sit-to-stand movement. - Janssen WG; Bussmann JB; Horemans HL; Stam HJ; Janssen, Wim G M; Bussmann, Johannes B J; Horemans, Herwin L D; Stam, Henk J (Medical & Biological Engineering & Computing, 2008)
Accelerometry is frequently used in movement analysis to assess body postures and motions. Here, we assessed the validity of ambulatory accelerometric measurement of the sit-to-stand (STS) movement duration. We compared accelerometric and opto-electronic assessment of the STS movement duration under four conditions (comfortable, slow, fast movement and exaggerated trunk flexion) with six healthy subjects and six subjects with stroke who performed movements six times under each condition. Accelerometric and opto-electronic data of STS movement duration were strongly related (r = 0.98). Accelerometry showed a fixed bias of 0.07 s (95% CI 0.008, 0.141) in healthy subjects and 0.32 s (95% CI 0.223, 0.422) in stroke subjects. In healthy subjects, a significant negative proportional bias of 0.1 was detected (95% CI -0.160, -0.032). Accelerometry showed discriminative validity in comparing stroke subjects to healthy subjects, and in comparing speed conditions. Our results indicate that accelerometry can provide valid data on the STS movement duration, furthermore during its use additional information on the STS movement, such as balance control, can be recorded.